IS OLODUMARE, GOD IN YORUBA BELIEF, GOD? - Benson O. Igboin (Sekolah Tinggi Agama Islam Sadra, 2014)
The question whether Olodumare, God in Yoruba belief, as Bolaji Idowu translated it, is God is a tortuous one. It is so because the concept of, and the belief in, Olodumare are undergoing circuitous strings of analysis that tempt one to answer the question in three fundamental episodic phases. The first came from the Western anthropologists who advertently or inadvertently ‘misconceived’ Olodumare, as completely less than a God; the second stage championed by foremost Africanist/ Yoruba theologians ‘promoted’ Olodumare to the ‘status’ of a God or rather insisted that Olodumare is God; while the decolonisation school is currently divesting Olodumare of so-called Hellenised garb of the second period, and casting ‘true’ images of him. Each of these ‘truths’ about Olodumare has serious ancillary questions that affect the overall understanding of Olodumare. This study interrogates the claims of three recent decolonisation philosophers, and reveals that their casting of Olodumare is inconsistent one with another. It concludes that before any incontrovertible concept of Olodumare could be reached, alternative translational (linguistic) equivalents true to the Yoruba theology and true to Christianity must be adopted; otherwise the questions raised might yet remain unanswered, while Idowu’s thesis still suffices